ULTRASOUND MONITORING IN THE EVALUATION OF THE FUNCTIONAL STATE OF A KIDNEY TRANSPLANT AT DIFFERENT IMMUNOSUPPRESSION THERAPIES - L.E. Belyaeva; V.A. Sandrikov; M.M. Kaabak; V.I. Sadovnikov; E.N. Platova; N.N. Babenko (Union of pediatricians of Russia, 2009)
This article covers one of the most important spheres in medicine - transplantation of a kidney from a live relative donor. The appearance of new generation immunosuppressive medicines has made it possible to boost the survivability of both the kidney and the recipient. The present research has allowed the authors to evaluate the functional state of a kidney transplant at the use of different immuno-suppression protocols (induction therapy with alemtuzumab in the first group and with daclizumab in the second one) by means of a non invasive examination method. Moreover, the authors have defined ultrasound signs of transplant rejection depending on the type (interstitial or vascular).Key words: kidney transplantation, transplant dysfunction, evaluation of the transplant function, immunosuppression.